Теорія змов та біотероризм російської пропаганди - Мацишина, Ірина Віталіївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The study analyzes the role of conspiracy theory on the example of the topic of biological weapons produced in Ukraine with the help of the United States. The Russian information resource “РИА Новости” was analyzed and key topics were highlighted. It is noted that Russian political propaganda is actively promoting this narrative to the Russian audience in order to justify armed aggression on the territory of Ukraine. These false claims are intended to create an artificial image of threat and hostility, aimed at undermining confidence in international partnerships and creating a negative image of Ukraine. The study of this propaganda campaign reveals the mechanisms of information warfare and emphasizes the importance of critical thinking to overcome disinformation.